(untitled) (International Conference on Education, Psychology and Humanities, 2026)
The increasing demands placed on university students require the development of both physical fitness and psychological resilience. Among female students, improving self-confidence, emotional stability, physical preparedness, and self-defense skills has become an important objective of modern physical education. Hand-to-hand combat training represents an effective educational tool that combines physical exercise with psychological conditioning. This study aims to determine the effectiveness of hand-to-hand combat training in improving the physical and psychological readiness of female university students. The research was conducted during the 2025–2026 academic year and involved 80 female students aged 18–22 years. The participants were divided into a control group (n=40), which followed the traditional physical education curriculum, and an experimental group (n=40), which participated in a structured hand-to-hand combat training program for five months. Physical preparedness was assessed through speed, strength, endurance, flexibility, agility, and coordination tests, while psychological readiness was evaluated using standardized questionnaires measuring self-confidence, stress resistance, emotional stability, and motivation. The results demonstrated statistically significant improvements (p<0.05) in all measured variables among the experimental group compared with the control group. The greatest improvements were observed in agility, reaction speed, self-confidence, and stress resistance. The findings indicate that systematic hand-to-hand combat training serves as an effective pedagogical means for developing both physical and psychological readiness among female university students. The study also provides practical recommendations for integrating hand-to-hand combat elements into university physical education programs.